Sensitivity of some human pathogenic yeasts and systemic fungi to myxin. - Sekhon, A S (1975)
Myxin, a relatively new antibacterial and antifungal antibiotic, produced by a species of Sorangium, was used to investigate its effectiveness against some yeasts and dimorphic fungi associated with human diseases. Results indicated that the minimal fungicidal concentrations (MFC) of myxin for Candida albicans, C. krusei, C. parapsilosis, C. tropicalis, and Torulopsis glabrata were 0.39-6.25 mug/ml, and for C. guilliermondii and C. tropicalis 12.5-25 mug/ml. The MFC for Blastomyces dermatitidis and Sporothrix schenckii was 0.195 and 6.25 mug/ml, respectively. The MFC for these two systemic fungi for amphotericin B (fungizone) was 0.39-0.78 and 6.25 mug/ml. It seems that myxin is more effective against B. dermatitidis than amphotericin B. The isolate of Coccidioides immitis was found to be very sensitive to myxin (MFC, 0.78-1.56 mug/ml).